Acclimatization in the bay scallop Argopecten irradians along a eutrophication gradient: insights from heartbeat rate measurements during a simulated hypoxic event. Issue 1 (2nd January 2021) - Gurr, Samuel J.; Dwyer, Ian P.; Goleski, Jennifer; Lima, Fernando P.; Seabra, Rui; Gobler, Christopher J.; Volkenborn, Nils
ABSTRACT: Coastal hypoxia can negatively impact shellfish, but it is unclear if exposure to intensifying diel-cycling hypoxia alters shellfish susceptibility to severe hypoxic events in late summer. In this study, bay scallops (Argopecten irradians) were acclimatized for 50 days at 5 sites along a eutrophication gradient, where scallops rarely, occasionally and frequently encountered hypoxic conditions. In a laboratory experiment, scallops were then exposed to a 24-h hypoxic event and heartbeat rates were recorded with non-invasive infrared sensors during the initial oxygen decline, during extended hypoxia, and for one hour after re-establishment of normoxia. Irrespective of acclimatization site, scallops sustained increased heartbeat rates during hypoxia, but cardiac responses were less pronounced in scallops that frequently encountered hypoxia during acclimatization. This study suggests that cardiac responses to changes in dissolved oxygen concentrations can be affected by exposure history, which may have important ramifications for scallop ecophysiology and resilience in dynamic coastal environments.